Assessing Credit Gaps in CESEE Based on Levels Justified by Fundamentals – A Comparison Across Different Estimation Approaches - Mariarosaria Comunale; Markus Eller; Mathias Lahnsteiner (Oesterreichische Nationalbank (OeNB), 2020)
Relying on a rich panel regression framework, we study the role of different "fundamental" credit determinants in Central, Eastern and Southeastern European (CESEE) EU Member States and compare actual private sector credit-to-GDP ratios to the derived fundamental levels. It turns out that countries featuring positive credit gaps at the start of the global financial crisis (GFC) have managed to adjust their credit ratios downward toward levels justified by fundamentals, but the adjustment is apparently not yet complete in all countries. In addition, negative credit gaps have emerged or widened in most countries that had seen credit levels close to or below the fundamental levels of credit at the start of the GFC. The estimated speed of adjustment implies that at the end of the review period, there was still a rather long way to go for countries with very large credit gaps.
Keywords: C33; E44; E51; G01; G21; O16; 330; private sector credit; fundamental level of credit; bank lending; global financial crisis; financial development; static heterogeneous panel model; panel error correction model